Wavelength-tunable thulium-doped fiber laser with sampled fiber Bragg gratings. (December 2019) - Zhang, Luna; Yan, Fengping; Feng, Ting; Han, Wenguo; Bai, Yan; Bai, Zhuoya; Cheng, Dan; Zhou, Hong; Suo, Yuping
Highlights: A wavelength-tunable Tm 3+ -doped fiber laser with two SFBGs has been proposed. A significant 14.44 nm wavelength range from 1942.09 to 1956.53 nm was achieved. The OSNRs of different wavelengths were 45–58 dB at a pump power of 3.67 W. The wavelength shift and power fluctuation were less than 0.03 nm and 0.46 dB. Abstract: A continuous wave (CW) wavelength-tunable Tm 3+ -doped fiber laser with two sampled fiber Bragg gratings (SFBGs) has been proposed and demonstrated. This proposed laser is stable operating with a significant 14.44 nm wavelength range from 1942.09 nm to 1956.53 nm due to the Vernier effect. The laser OSNRs of different wavelengths ranged from 45 dB to 58 dB at a launched pump power of 3.67 W. The wavelength shift and power fluctuation were less than 0.03 nm and 0.46 dB, respectively. An 8.62% slope efficiency was achieved using a grating for laser extracting. To the authors' knowledge, this is the first time that a wavelength-tunable Tm 3+ -doped fiber laser with two SFBGs has been demonstrated.